Developing and testing models for benchmarking and moderation of assessment for private higher education providers. - Tuovinen, Juhani; Dachs, Terry; Fernandez, Jane; Morgan, David; Sesar, Jasmina (Office for Learning and Teaching, 2015)
Numerous previous studies have focussed on benchmarking in universities. The small-sized, private higher education provider institutions' needs have not received similar level of attention even though it is expected that the private higher education sector will expand to contribute up to 30% of the total higher education enrolments by 2020 (Shah & Lewis, 2010). In order to address this gap, this project sought to examine the needs of these smaller institutions, testing the lessons learned in practice and thus improve their quality of capability in the context of Australian higher education. This project sough to benchmark assessment moderation in four colleges by applying the Garlick and Pryor (2004) model of benchmarking. This benchmarking approach contrasts with prior benchmarking approaches, as typified by the McKinnon at al (1999) model where information is sought from an institution, e.g. a university, for the purpose of senior management decision-making. Instead the Garlick and Pryor model argues for an improvement and learning focus for the staff at the coalface. This is a report from the project. [Executive summary, ed]